Library Development Strategy in Meeting Needs Nagari Community Information - Bachtiar Sinuraya (Fakultas Dakwah dan Ilmu Komunikasi, 2022)
Ease of access to public information is currently forcing the library to develop service innovations. The presence of various types The library is one of the impacts of easy access to information. Conventional libraries are now metamorphosed into libraries digital and even bookless libraries. The physical changes of this library are proof that the library is constantly evolving to meet the needs its users. Hybrid libraries are becoming one of the most popular form types today This is widely implemented in various libraries. Hybrid library become a balancer for the needs of the community who take advantage of the collection print and digital collections. Acceleration of library services is not just about physical services, but also on services that encourage people to think and behave intellectually